Differences in nicotine dependence, smoke exposure and consumer characteristics between smokers of machine-injected roll-your-own cigarettes and factory-made cigarettes - Joseph, Sarah (Drug Alcohol Depend, 2018)
BACKGROUND: Consumption of machine-injected roll-your-own (RYO) filtered cigarettes made from pipe tobacco increased almost 7-fold from 2008–2011 in the United States. METHODS: We used data from the Pennsylvania Adult Smoking Study to compare the differences in sociodemographic, smoking topography, nicotine dependence, and cotinine levels between 280 smokers using factory made (FM) cigarettes and 68 smokers using RYO cigarettes. RESULTS: RYO smokers were older (41 vs. 37, P=0.053), had significantly lower levels of income (P<0.001) and education (P=0.007), and were less likely to be fully employed (P=0.009). RYO smokers consumed more cigarettes per day [CPD] (21 vs. 15, P<0.001), and had a higher mean score on the Fagerström Test for Cigarette/Nicotine Dependence (5.2 vs. 4.1, P<0.001). The main reasons for choosing RYO cigarettes were the lower cost (68%) and believed they are less harmful (12%). The average cost per pack of FM cigarettes was $5.74 vs. $1.13 for RYO. In multiple regression analyses, RYO smokers had significantly lower cotinine levels across all levels of CPD. Among smokers of king-size cigarettes, mean interpuff interval (P<0.05) and total smoke duration (P<0.01) per cigarette was significantly greater in RYO smokers. In laboratory measurements, RYO cigarettes contained more tobacco by weight than FM cigarettes, but weight varied by both tobacco and cigarette tube brands. CONCLUSIONS: Machine-injected RYO cigarettes made from pipe tobacco are cheaper than FM cigarettes but may have higher abuse liability. Smokers who might otherwise reduce their cigarette consumption or quit altogether may continue to smoke RYO cigarettes due to their affordability.